Thymosin beta 4 induces significant changes in the plasma miRNA profile following severe traumatic brain injury in the rat lateral fluid percussion injury model. (31st May 2018) - Osei, Jennifer; Kelly, William; Toffolo, Kathryn; Donahue, Kaitlynn; Levy, Bennet; Bard, Jonathan; Wang, Jianxin; Levy, Elad; Nowak, Norma; Poulsen, David
ABSTRACT: Objectives : Thymosin beta 4 (Tβ4) has demonstrated neuroprotective potential in models of neurlogical injury. The neuroprotective potential of Tβ4 has been associated with increased miR-200a and miR-200b within the brain following stroke. Here we tested the hypothesis that Tβ4 treatment could also alter miRNA profiles within the plasma following severe traumatic brain injury (TBI). Methods : We used the rat lateral fluid percusion injury model of severe TBI to test this hypothesis. Highly sensitive and quantitative droplet digital polymerase chain reaction (ddPCR) was used to measure the plasma concentrations of miR-200 family members. In addition, we conducted RNAseq analysis of plasma miRNA to further identify changes associated with TBI and treatment with Tβ4. Results : ddPCR demonstrated that miR-200a-3p andmiR-200b-3p were both significantly increased in plasma following treatment with Tβ4 after severe TBI. RNAseq analysis suggested that miR-300-3p and miR-598-3p increased while miR-450-3p and miR-194-5p significantly decreased following TBI. In contrast, miR-194-5p significantly increased in Tβ4 treated rats following TBI. In addition, we identified nine plasma miRNAs whose expression significantly changed following treatment with Tβ4. Conclusions : Tβ4 treatment significantly increased plasma levels of miR-200a-3p and miR-200b-3p, while RNAseq analysis identified miR-194-5p as a candidate miRNA that may be critical for neuroprotection.